A LITERATURE STUDY ON THE DETERMINANTS OF CONSUMER SWITCHING BEHAVIOR - Rahayu Lestari; Resti Hardini; Tri Waluyo; Kumba Digdowiseiso; Khalid Farooq (PT. Radja Intercontinental Publishing, 2024)
This study seeks to investigate the factors that determine Consumer Switching Behavior by examining the influences on consumers' choices to switch between brands, products, or service providers. In order to ensure the ongoing success of a business, it is crucial to possess a comprehensive comprehension of consumer switching behavior, given the swiftly evolving market dynamics. The research methodology employed in this study utilizes a Systematic Literature Review (SLR) approach to systematically gather, curate, and analyze relevant findings from existing literature. The study findings revealed that consumer switching is primarily driven by factors such as shifting preferences, economic considerations like price and value, the costs associated with switching, negative experiences, social influence, and the reputation of brands as communicated through social media. The findings and analysis demonstrate that a more profound comprehension of these variables can assist companies in formulating marketing strategies that are both more efficient and adaptable to evolving consumer demands. Ultimately, this research greatly enhances our comprehension of consumer switching behavior dynamics, fortifies the foundation for the formulation of adaptable business strategies, and guarantees the competitiveness of companies in a fiercely competitive market. This research offers valuable insights for companies to enhance customer retention strategies and establish robust consumer relationships by examining the factors that influence consumers' decisions to switch.